Since the primary storage nutrients in diatoms consist of lipid, they are potential for the industrial fatty acid production. High value fatty acids include arachidonic acid, eicosapentaenoic acid and docosahexaenoic acid. This study aimed to analyze fatty acid synthesis by Chaetoceros gracilis diatom during growth. There was a large increase in lipid yield from 4pg cell-1 mass of lipid per cell at the exponential phase to 283pg cell-1 at stationary phase. The lipid concentrations also increased - ALBERTA RIKA PRATIWI; DAHRUL SYAH; LINAWATI HARDJITO; LILY MARIA GORETTI PANGGABEAN; MAGGY THENAWIDJAJA SUHARTONO (Bogor Agricultural University, Indonesia, 2009)
Since the primary storage nutrients in diatoms consist of lipid, they are potential for the industrial fatty acid production. High value fatty acids include arachidonic acid, eicosapentaenoic acid and docosahexaenoic acid. This study aimed to analyze fatty acid synthesis by Chaetoceros gracilis diatom during growth. There was a large increase in lipid yield from 4pg cell-1 mass of lipid per cell at the exponential phase to 283pg cell-1 at stationary phase. The lipid concentrations also increased significantly from the stationary phase to the death phase, but not significantly from the end exponential phase to the stationary phase. The relative percentage of saturated fatty acid (SAFA) of the total fatty acid was higher than that of monounsaturated fatty acid (MUFA) and polyunsaturated fatty acid (PUFA) at all of growth phase. The highest PUFA was found at stationary phase at the same time when SAFA was being the lowest. The majority of SAFA was palmitic acid (24.03-40.35%). MUFA contained significant proportion of oleic acid (19.6-20.9%). Oleic acid, linoleic acid and α-linolenic acid were found at every stage growth. These fatty acids are considered as precursor for production of long chain PUFA-Docosahexaenoic acid (DHA/22:6ω3) through series of desaturation and elongation step with all of desaturase enzyme (Δ8-D, Δ9-D, Δ12-D, Δ15-D, Δ17-D, Δ6-D, Δ5-D, and Δ4-D) and elongase enzyme (E). Key words: Chaetoceros gracilis, fatty acid, synthesis, saturated fatty acid (SAFA), monounsaturated fatty acid (MUFA), polyunsaturated fatty acid (PUFA)